Comparison of the Treatment Efficacy of Rituximab and Plasmapheresis/Intravenous Immunoglobulin Combination with Historical Control in Chronic Antibody Mediated Rejection - ATA, PINAR (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2017)
OBJECTIVE: Chronic antibody mediated rejection (CAMR) is a major therapeutic challenge for achieving long-term graft survival; treatment options are limited to several anti-humoral interventions. MATERIAL and METHODS: Efficacy of rituximab combination therapy was retrospectively investigated by comparison with a historical control group for allograft function at six month and overall graft survival/dysfunction. The inclusion criterion was biopsy proven chronic AMR according to the Banff 2007 classification. Nineteen patients found eligible, rituximab group had nine patients (rituximab, plasmapheresis and low dose IVIG); control group had ten recipients. Predictive factors for graft failure also investigated according to Banff scores and renal functions. RESULTS: None of the outcomes were exposed significant efficacy of rituximab, although better treatment response at sixth month (55% vs. 40%, p= 0.51), fewer overall graft failures (33% vs. 60%, p= 0.25) and dysfunctions (66% vs. 80%, p= 0.52). Overall, 47% of patients suffered graft failure. Advanced transplant glomerulopathy was found in 90% of biopsies (all scored = 2). Peritubular capillaritis score (1.67 +/- 0.87 vs. 0.70 +/- 0.94, p= 0.04) and interstitial inflammation score (1.78 +/- 0.44 vs. 1.00 +/- 0.47, p= 0.004) were significantly higher in recipients who suffered graft failure. CONCLUSION: Rituximab could not sufficiently prevent further deterioration of allograft and failed to improve allograft survival in CAMR, especially after settlement of the irreversible transplant glomerulopathy.
Keywords: Kidney transplantation; Chronic antibody mediated rejection; Transplant glomerulopathy; Rituximab; TRANSPLANT GLOMERULOPATHY; RENAL-ALLOGRAFTS; PATHOLOGY; THERAPY; INJURY; RISK; IVIG